KITAB FIKIH ULAMA BANJAR Kesinambungan Dan Perubahan Kajian Konsep Fikih Lingkungan - Sukarni, Sukarni (Universitas Islam Negeri Raden Intan Lampung, 2015)
FIQH TEXTS BANJARESE ULAMA CONTNUITY AND DEVELOPMENT STUDY OF FIQH ECOLOGY: Fiqh texts play an important role in the Muslim community throughout the ages. Fiqh texts become the code of conduct for Muslim to make their deeds valid and in accordance with the teachings of Islam. Fiqh texts as intellectual products have an important role to determine the level of creation and as means to observe the progress of the intellect of a Muslim community. In addition, fiqh texts produced can be a hint towards a particular school of thought and as critical study materials to perform continuity and development of intellectual work. Banjarese Ulama (from Banjarese ethnic) are known by their religiosity. The work in the field of jurisprudence was also born from them since Sabilal Muhtadin in the 18th century until Mabadi Ilmu ‘Fiqh of the 20th century. However, the continuity of the intellectual work that appreciates for the environment, especially on water ecology, which characterizes the ecology of Banjar, is inadequate. This shows the “unthinkable” in an intellectual creation, as described in the results of this study.